Los derechos humanos de los niños y niñas con discapacidad que no tienen cuidados parentales o están en riesgo de perderlos - Bregaglio Lazarte, Renata Anahí (2019)
This paper raises the need of assessing a disability perspective in the Peruvian regulation related to children who lack parental care or who is under risk of losing it. To aim this objective, the authors develop the concept of intersectionality between children and disability and then identify the different exercise rights by these children that require the incorporation of this approach where is necessarily to adopt new measures.